Respuesta :

Answer:

  1. a
  2. d
  3. a
  4. c
  5. a
  6. b
  7. a
  8. b
  9. c
  10. a

Step-by-step explanation:

[tex] {a}^{0} = 1 \\ \frac{ {a}^{n} }{ {a}^{m} } = {a}^{n - m} \\ {a}^{n} \times {a}^{m} = {a}^{n + m} [/tex]

Answer:

[tex]1. \: b. \\ 2. \: a. \\ 3. \: a. \\ 4. \: c. \\ 5. \: a. \\ 6. \: b. \\ 7. \: a. \\ 8. \: b. \\ 9. \:c. \\ 10. \: a. [/tex]

Step-by-step explanation:

[tex]1. \: {9}^{0} = 1 \\ \\ 2. \: \frac{ {x}^{5} }{ {x}^{3} } = {x}^{5 - 3} = {x}^{2} \\ \\ 3. \: {a}^{4} \times {a}^{2} = {a}^{4 + 2} = {a}^{6} \\ \\ 4. \: \frac{ {x}^{5} }{ {x}^{5} } = 1 \\ \\ 5. \: {( {x}^{2} })^{3} = {x}^{2 \times 3} = {x}^{6} \\ \\ 6. \: \frac{ {6}^{5} }{ {6}^{4} } = {6}^{5 - 4} = {6}^{1} = 6 \\ \\ 7. \: {( {a}^{2} {b}^{3} )}^{0} = 1 \\ \\ 8. \: ( {2}^{2} ) ({3}^{2} ) = (4)(9) = 36 \\ \\ 9. \: ( {m}^{2} )( {m}^{5} ) = {m}^{5 + 2} = {m}^{7} \\ \\ 10. \: \frac{ {x}^{10} }{ {x}^{2} } = {x}^{10 - 2} = {x}^{8} [/tex]

ACCESS MORE